Increased Frequency of Inter-Subtype HIV-1 Recombinants Identified by Near Full-Length Virus Sequencing in Rwandan Acute Transmission Cohorts - Umviligihozo, Gisele; Muok, Erick; Nyirimihigo Gisa, Emmanuel; Xu, Rui; Dilernia, Dario; Herard, Kimberley; Song, Heeyah; Qin, Qianhong; Bizimana, Jean; Farmer, Paul; Hare, Jonathan; Gilmour, Jill; et al. (Frontiers in Microbiology, 2021)
Most studies of HIV-1 transmission have focused on subtypes B and C. In this study, we determined the genomic sequences of the transmitted founder (TF) viruses from acutely infected individuals enrolled between 2005 and 2011 into IAVI protocol C in Rwanda and have compared these isolates to viruses from more recent (2016–2019) acute/early infections in three at risk populations – MSM, high risk women (HRW), and discordant couples (DC). For the Protocol C samples, we utilized near full-length single genome (NFLG) amplification to generate 288 HIV-1 amplicons from 26 acutely infected seroconverters (SC), while for the 21 recent seroconverter samples (13 from HRW, two from DC, and six from MSM), we PCR amplified overlapping half-genomes. Using PacBio SMRT technology combined with the MDPseq workflow, we performed multiplex sequencing to obtain high accuracy sequences for each amplicon. Phylogenetic analyses indicated that the majority of recent transmitted viruses from DC and HRW clustered within those of the earlier Protocol C cohort. However, five of six sequences from the MSM cohort branched together and were greater than 97% identical. Recombination analyses revealed a high frequency (6/26; 23%) of unique inter-subtype recombination in Protocol C with 19% AC and 4% CD recombinant viruses, which contrasted with only 6.5% of recombinants defined by sequencing of the pol gene previously. The frequency of recombinants was significantly higher (12/21; 57%) in the more recent isolates, although, the five related viruses from the MSM cohort had identical recombination break points. While major drug resistance mutations were absent from Protocol C viruses, 4/21 of recent isolates exhibited transmitted nevirapine resistance. These results demonstrate the ongoing evolution and increased prevalence of recombinant and drug resistant transmitted viruses in Rwanda and highlight the importance of defining NFLG sequences to fully understand the nature of TF viruses and in particular the prevalence of unique recombinant forms (URFs) in transmission cohorts.